Modeling of Freezing Process for Biological Objects Using Low Cooling Rates - Mischenko, A. G. (Problems of Cryobiology and Cryomedicine, 2007)
Existing mathematical models of heat exchange were analyzed. There was chosen the model which more adequately describes the process of heat exchange for thermal block in the neck of Dewar vessel. Using the model the parameters of device enabling to apply the rates of heat exchange from 0.01 to 4°C/min down to various final temperatures from 0 to –70°C at passive cool-down of thermal block in Dewar vessel neck.